Design and social innovation in vulnerable communities (2012)
Industrial Design's responsibility is to design friendly environments for users that minimize the impact of proposed solutions ensuring that these will be regenerative and that they will give back more resources than the ones they have taken, always keeping in mind the improvement in societies' conditions. In a country of contrasts such as Colombia, social innovation is a challenge for disciplines with high social impact. For this reason the academy has been inclined to educate future professionals with high sense of social responsibility, searching always for sustainability, being understood as a tool that helps to mitigate current economic and social imbalances. This is why the Industrial Design Academic Program is looking forward to promoting solutions that face the future with a special emphasis on social responsibility, trying to intervene directly inparticular sectors of the society, as well as specific communities with a high vulnerability level.